2023
DOI: 10.1186/s43141-023-00490-0
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activities and GC/MS-based phytochemical analysis of two traditional Lichen species Trypethellium virens and Phaeographis dendritica

Abstract: Background Lichens are complex plants living in symbiotic relationship between fungi and algae. They are used for human and animal nutrition and are used in folk medicine in many countries over a considerable period of time. In the present study, various solvent extracts of Trypethelslium virens and Phaeographis dendritica were tested for their antioxidant and antimicrobial activity. Results The phytochemical analysis by GC/MS revealed phenolics (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…The lichen species used in our study showed antimicrobial activity against test microorganisms with diameter of the inhibition zone varying between 7-15 mm. There have been many studies examining the antimicrobial activities of lichens 4,8,12,15,21,31]. When all these literature informations are evaluated, inhibition zone diameter sizes in our findings are comparable with other studies.…”
Section: Antimicrobial Activities Of Lichens Disc Diffusion Methodssupporting
confidence: 87%
See 4 more Smart Citations
“…The lichen species used in our study showed antimicrobial activity against test microorganisms with diameter of the inhibition zone varying between 7-15 mm. There have been many studies examining the antimicrobial activities of lichens 4,8,12,15,21,31]. When all these literature informations are evaluated, inhibition zone diameter sizes in our findings are comparable with other studies.…”
Section: Antimicrobial Activities Of Lichens Disc Diffusion Methodssupporting
confidence: 87%
“…When the MIC values obtained in some studies examining the antimicrobial properties of various lichen species are compared, it is understood that our results are at an average level. (8,23,38).…”
Section: Mic Values Of Lichensmentioning
confidence: 99%
See 3 more Smart Citations